Problematic Areas of Host University Support Services for Short-Term Mobility Students - Perez-Encinas, Adriana; Rodriguez-Pomeda, Jesus; Josek, Mikuláš (Journal of International Students, 2017)
The growing numbers of mobile students over the years made the provision of student services a key topic of interest for higher education institutions. In order to offer a better experience for international students, it is important to be aware of and assess their needs in relation to different sets of support services. The data used in this paper were gathered through the ESNsurvey 2016 project, a research venture focused on the experiences of participants in short-term student mobility in Europe. Responses were collected from 12,365 international students, who have participated in a short-term (3-12 months) study period abroad mostly through Europe’s most promoted mobility program called ERASMUS+. For the purpose of this paper, the focus was only on the aspect of host university support services. The comments of 2,012 students about their experiences were analyzed using a probabilistic methodology known as Latent Dirichlet Allocation (LDA).